CREATING PERSONALIZED LEARNING PATHWAYS THROUGH ARTIFICIAL INTELLIGENCE: A COMPREHENSIVE STUDY - Xatamova Sojida Sobir qizi; Jo‘rayev Muhammadrahimxon Murod o‘g‘li (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: this paper explores the growing role of artificial intelligence in shaping modern education through the development of personalized learning pathways. Traditional instructional models often assume that all learners progress at the same pace and possess similar abilities, which leads to disengagement and uneven learning outcomes. Artificial intelligence introduces adaptive tools that adjust to the learner’s knowledge level, learning speed, and individual characteristics. This study reviews theoretical foundations supporting personalized learning, explains how AI systems function within educational environments, and highlights their advantages and challenges. It also addresses ethical considerations and future directions. The analysis demonstrates that while AI has the potential to significantly enhance learner-centered education, issues such as data privacy, algorithmic bias, teacher preparedness, and equitable access must be carefully managed.